Cadastro Ambiental Rural e Reserva Legal: avaliação e aplicações dos dados espaciais do SICAR - Dantas, Guilherme David (2020)
The current Brazilian Forest Code (CFB, in Portuguese abbreviation), instituted by the Law no. 12,651 (BRAZIL, 2012), is a legal instrument in which the Legal Reserve (LR) appears as an important mechanism in the context of preserving the remnants of native vegetation. One of the innovations of this law was the implementation of a nationwide electronic system for the management of environmental information on rural properties, called Rural Environmental Registry (CAR, in Portuguese abbreviation). This one makes publicizes spatial data of rural properties registered in the system and allows their uses for various analyzes. The present study aimed to verify and evaluate the information of native vegetation cover and of LR declared in CAR, in order to evaluate the efficiency of the system and to use Landscape Metrics to characterize the spatial distribution of these areas, considering the recovery potentials. The Ribeirão Douradinho watershed, located in the mesoregion of Triângulo Mineiro and Alto Paranaíba, in Minas Gerais, Brazil, comprised the spatial analysis of the data in this research. The operational procedures consisted the Remote Sensing (RS) techniques and Geographic Information Systems (GIS) for organizing, processing and evaluating spatial data, in addition to specific programs for calculating Landscape Metrics on the obtained results. It was found that, in July 2018, the respective basin had 90% of its area filled by registered rural properties, with an overlap rate of 2.7% between the respective registrations; the LRs, on the other hand, obtained an overlap index of 1.0%. In relation to the declared data on land cover, information was omitted in 11.9% of the total area in the registers. Regarding the veracity of the declared information on native vegetation cover, 8% of the total declared area was composed of non-true data and 12% are related to areas without information. In the LRs, 20% of the declared area proved to be untrue and 10% without information, which represents 30% of the total declared area. The main observation obtained through the results of Landscape Metrics indicated that the recovery of vegetation on the LRs and Permanent Preservation Areas (APP, in Portuguese abbreviation) located in consolidated areas would imply a 23% growth over the current remnants of native vegetation. The average size of fragments of native vegetation would increase in 77%, and the average distance of fragments would be reduced in 17%. Despite the inconsistency in the data of a certain part of CAR, it brought great advantages in the availability of land cover information of rural properties in an organized and integrated way. The GIS resources and the orbital images on the CAR spatial data provided parameters of quality and veracity of the information, which allows to evaluate the efficiency of the system. It is worth mentioning that Landscape Metrics proved to be effective as a tool for exploring these data, with the comparison of current and future scenarios about the LRs and the remnants of native vegetation.